2008
DOI: 10.2304/ciec.2008.9.2.95
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Literacy in English Language in Singaporean Preschools: Exploring Teachers' Beliefs about What Works Best

Abstract: Singaporean preschool teachers are responsible for preparing their young students for a formal education that is predominantly conducted in English. What these teachers believe about how young children learn English literacy skills is important to study, especially when much of the research is situated in very different contexts. Talking to teachers about their roles is a way of examining interpretations of 'effective' teaching and learning in terms of actual literacy pedagogy. Three broad categories were disc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…In a nutshell, it seems that having opportunities to continue to learn informally about pedagogy within the workplace, both individually and especially in collaboration with others, contributes to enhance Singapore preschool teachers' perceived competencies regarding their ability to successfully teach students and motivate them. The lack of relationship between informal PD and classroom management self-efficacy beliefs might be due to the fact that preschool teachers in Singapore rarely encounter challenges related to discipline or disruptive behaviors in the classroom (Lim & Torr, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…In a nutshell, it seems that having opportunities to continue to learn informally about pedagogy within the workplace, both individually and especially in collaboration with others, contributes to enhance Singapore preschool teachers' perceived competencies regarding their ability to successfully teach students and motivate them. The lack of relationship between informal PD and classroom management self-efficacy beliefs might be due to the fact that preschool teachers in Singapore rarely encounter challenges related to discipline or disruptive behaviors in the classroom (Lim & Torr, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Two separate surveys of teachers' beliefs in English literacy instruction within Singapore's multi-cultural and multi-lingual context found that kindergarten teachers either subscribed to a child-centered approach (Lim & Torr, 2008) or an eclectic mix of child-centered and teacher-centered approaches (Lim & Torr, 2007). These findings suggest that it is not evident that the espoused beliefs of Singaporean kindergarten teachers were in conflict with Western notions of ECE approach.…”
Section: Factors Influencing Beliefs and Practicesmentioning
confidence: 94%
“…A considerable amount of studies has found that early childhood teachers' reported beliefs in child-centered or developmentally appropriate practices were often not manifested in their teaching practices, which tended to be more teacher-centered (Kwon, oriented and highly competitive (Ang, 2006(Ang, , 2014Lim & Torr, 2008). Ebbeck and Gokhale (2004) reported that most Singaporean parents prefer preschool education to be academic-oriented in order to help their children to be academically ready for future scholastic achievement and success.…”
Section: Introductionmentioning
confidence: 99%
“…But concerns have been raised regarding the cultural conflicts arising from the importation of Western curriculum approaches and pedagogical practices into Asian contexts due to the incompatibility of the educational ideologies and cultural norms embedded in the two dissimilar Western and Eastern traditions and contexts (Hsieh 2004;Lee and Tseng 2008;Li et al 2011;McMullen et al 2005). In a similar fashion, the influence of Western philosophies and theories on how children learn and should be taught in Singapore's NEL Framework has been claimed to run counter to the traditional cultural beliefs and the inherent curriculum priorities held by teachers and parents in a largely Chinese society with Confucius influence (Ang 2006(Ang , 2014Lim-Ratnam 2013;Lim and Torr 2008). There is thus a concern that efforts to downplay a formal and academically focused kindergarten curriculum are at odds with the premium value Singaporean parents placed on academic achievement and their expectations of their children to be well prepared for primary school in order to meet the demands of a highly (Ang 2006(Ang , 2014Ebbeck and Chan 2011;Nyland and Ng 2016).…”
Section: Use Numbers In Daily Experiencesmentioning
confidence: 99%